Intervención optométrica en paciente masculino de 16 años de edad con pseudomiopía - Álava Vinces, Karla Denisse (2024)
The project focuses on a 16-year-old male patient diagnosed with pseudomyopia, a condition in which distance vision is affected due to a transient refraction problem. The main objective of optometric intervention is to address this problem and improve the visual quality of said patient. This includes a detailed evaluation of visual acuity, refraction, accommodation, and visual function to understand the underlying cause of pseudomyopia in the patient. Based on these results, a personalized treatment plan will be designed that may include vision therapy, prescription of corrective lenses or specific vision exercises. Results: once each of the optometric examinations were performed, it was possible to detect that the patient has pseudomyopia due to accommodative excess for which continuous monitoring is planned to monitor the progression of the treatment and adjust it as necessary. Conclusion: It is expected that, through this comprehensive optometric intervention, the patient will experience a significant improvement in their distance and near vision, reducing the symptoms of pseudomyopia and improving their overall visual quality of life through the established treatment.